2022
DOI: 10.1021/acssuschemeng.1c05239
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Bacterial Pelletized Cultivation Platform in Rhodococcus opacus PD630 Enhanced Lipid Productivity and Simplified Harvest for Lignin Bioconversion

Abstract: Pelletized liquid cultivation has been widely explored because of its advantages in biomanufacturing, such as easier biomass harvesting, higher product yield, and lower medium viscosity and energy consumption. In this study, we discovered that the nonfilamentous bacterium Rhodococcus opacus PD630 could form pellets during the fermentation of alkaline pretreatment liquor containing lignin as a carbon source. This discovery advanced our understanding of bacterium pelletization, as only filamentous fungi and fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
1
Order By: Relevance
“…The method used to generate the sorghum APL feedstock is well known to solubilize easily cleavable aromatics from plant cell walls, without the breakdown of the carbohydrate and lignin polymers in the biomass ( 28 ). We showed that N. aromaticivorans can grow in the presence of sorghum APL alone, unlike previous studies which have supplemented lignocellulosic APL with minerals ( 38 43 ) and/or nitrogen/carbon sources ( 38 , 40 , 44 , 45 ). We also found that N. aromaticivorans produces nearly the same amounts (normalized to dry cell weight) of carotenoids and CoQ 10 when grown on sorghum APL as when grown in a defined medium containing vanillate ( Fig.…”
Section: Discussioncontrasting
confidence: 90%
“…The method used to generate the sorghum APL feedstock is well known to solubilize easily cleavable aromatics from plant cell walls, without the breakdown of the carbohydrate and lignin polymers in the biomass ( 28 ). We showed that N. aromaticivorans can grow in the presence of sorghum APL alone, unlike previous studies which have supplemented lignocellulosic APL with minerals ( 38 43 ) and/or nitrogen/carbon sources ( 38 , 40 , 44 , 45 ). We also found that N. aromaticivorans produces nearly the same amounts (normalized to dry cell weight) of carotenoids and CoQ 10 when grown on sorghum APL as when grown in a defined medium containing vanillate ( Fig.…”
Section: Discussioncontrasting
confidence: 90%
“…Pelleted culture has been extensively studied for its high yield and ease of product collection, the low viscosity of the medium, and thus low energy consumption ( Nair et al, 2016 ). Xu et al (2022) reported for the first time the spontaneous formation of pellets by bacteria during fermentation with an alkaline treatment solution of maize stover as the carbon source, even in the absence of added chemical coagulants. It was found that the lipid content of the pellets was higher than that of the suspended biomass at low nitrogen concentrations.…”
Section: Bio-conversion Of Lignin To Lipidsmentioning
confidence: 99%